(Antioxidants : Mechanism of Action and Its Function in Human Body) - Hendra Wijaya; Lukman Junaidi (Warta Industri Hasil Pertanian, 2011)
Antioxidant could be defined by several means. Antioxidant is a substance that could postpone and delay oxidation of molecule substrate in human body ,i.e ; protein ,carboydtrate,lipid and DNA, by oxidant. antioxidant that works in the human body's biological system is called a  biological antioxidant Biological antioxidants can be grouped into :1) enzymatic antioxidants (endogenous) ,2) non-enzymatic antioxidants (endogenaous) and, 3) antioxidants from food (exogenous0.Enzymatic antioxidants (endogenous) include superoxide dismutase ,catalase ,glutathione peroxidase, glutaredoksin, tioredoksin, peroksiredoksin ,and coenzyme q10.non-enzymatic antioxidants (ENDOGENOUS) are carotenoids,vitamin E  and vitamin C those antioxidants are able to work in hydrophobic and hydrophilic cellular environment so as to from a strong network of cooperation in preventing the occurrence of oxidative damage .some of the functions of antioxidants in the human body that can be expressed are ; preventive defense the human body against oxidants ,strong defense system against free redicals ,prevent the occurrence atherosclerosis in blood vessels,regulation of metabolism such as disabling lipoksigenase.